2012
DOI: 10.1039/c2py20462b
|View full text |Cite
|
Sign up to set email alerts
|

Mild and efficient bromination of poly(hydroxyethyl acrylate) and its use towards ionic-liquid containing polymers

Abstract: International audienceAn original and mild bromination protocol allows a poly(hydroxyethyl acrylate) polymer synthesized by ATRP to be converted readily and quantitatively into its corresponding poly(bromoethyl acrylate) analogue. We show that the latter can be used as a common precursor towards ionic-liquid containing polymer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 30 publications
(43 reference statements)
4
23
0
Order By: Relevance
“…S2†). By analogy with previous studies, 14,16 the observed discrepancies between the two techniques were attributed to the branched nature of the polymer chains that leads to an overestimation of polydispersity indexes by GPC. 17 A minimal length of 80 units was found to be necessary for the target biological application, as our attempts to produce shorter chains resulted in a non-water soluble material.…”
Section: Resultssupporting
confidence: 70%
“…S2†). By analogy with previous studies, 14,16 the observed discrepancies between the two techniques were attributed to the branched nature of the polymer chains that leads to an overestimation of polydispersity indexes by GPC. 17 A minimal length of 80 units was found to be necessary for the target biological application, as our attempts to produce shorter chains resulted in a non-water soluble material.…”
Section: Resultssupporting
confidence: 70%
“…In the case of In1, the phosphonate moiety was introduced in its ethyl-protected form, using a straightforward two-step methodology. Then, the ethylphosphonate-(PIm1) and ethyl-terminated (PIm2) polymers were synthesized according to the same general methodology as described in a previous report [13]. This methodology relies on the following three-step sequence consisting of i) ATRP of hydroxyethylacrylate followed by ii) nucleophilic substitution of the pendant hydroxyl group with bromide ions and iii) addition of methylimidazole, resulting in quaternarization of the nucleophile ( Figure 1).…”
mentioning
confidence: 99%
“…The resultant polymer was precipitated in a mixture of hexane:isopropylalcohol (9:1), filtered, and dried in a vacuum oven at 40°C overnight. Our procedure is similar to that reported by Appukuttan et al 38 1 H NMR (CDCl 3 , 500 MHz, δ):…”
Section: Macromoleculesmentioning
confidence: 68%